Entrepreneurship: Creating and leading an Entrepreneurial Organization - Arya Kumar (New Delhi: Pearson, 2012)
A new venture or business always stands on the precarious ground of unpredictable challenges wherein it is constantly subjected to pressures from competition and the ever changing dynamics of the market. In this scenario, a venture can only be successful, if it is guided by an entrepreneur who measures situations insightfully and calculates the risks before taking a plunge. This book is about creating, managing and leading an entrepreneurial organization. The contents would help in inculcating an entrepreneurial mindset, developing entrepreneurial skills and equipping the reader with the basic knowledge and skills for launching and managing the growth of a venture. The teaching/learning of entrepreneurship require greater focus on experiential learning. Therefore, the book extensively emphasizes on experiential learning and a hands-on approach - 'learning by doing'. Book has cited a number of examples and given cases and exercises from Indian as also global contexts to make entrepreneurship learning an enjoyable experience.
Keywords: Entrepreneurship